Relationship of sweet taste perception to PROP (6-n-propylthiouracil) taster status, food preference, and consumption of selected young Filipino adults who are non-Alcoholic or alcoholic drinkers - Tangcueco, Vanessa Gayle T. (College of Home Economics, University of the Philippines Diliman, 2021)
The study aimed to assess the relationship between sweet taste intensity perception and PROP taster status, food preference and consumption, and nutrient intake of Filipino Youth alcoholic drinkers and nondrinkers. The participants (n=50) were classified into groups of drinkers and nondrinkers according to their alcohol use disorder identification test (AUDIT). In addition, the participants self-administered the food preference checklist and the 3-day food record. PROP taster status and sweet taste intensity perception was also determined using sensory evaluation of PROP/NaCl and sucrose solutions, respectively. Majority of the drinkers (n-26) comprised mainly of females (58%) while majority of the nondrinkers (n=24) were males (58%). PROP taster status of the participants showed that 14% were nontasters, 48% were medium tasters, and 38% were super tasters. No significant correlation (p>0.05) was found between sweet taste intensity perception between (a) PROP taster status, (b) food preference according to food groups, (c) food consumption and nutrient intake, and (d) drinker status. However, there was a significant negative correlation (p<0.05) between sweet taste intensity and preference for fried pork and fruit jams. Results of the study imply that sweet taste perception is not associated with alcohol consumption, PROP taster status, and food consumption and nutrient intake of Filipino youth. It would be interesting to evaluate the same parameters on older participants.